Tinjauan Sistematis Literatur Pengaruh Nilai Tukar Rupiah Terhadap Ekspor Indonesia: A Systematic Literature Review of the Impact of the Rupiah Exchange Rate on Indonesian Exports - Andrian Januar; Fikri Andika; Fitria Beta Sundari; Zian Fachrian (Jurnal Bisnis dan Ekonomi, 2026)
Objective : This study aims to analyze and synthesize the findings of previous research on the impact of the rupiah exchange rate on Indonesia’s exports, as well as to identify similarities, differences, and research gaps that can still be explored. Methods : This study employed a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The research data consisted of 10 scientific articles published between 2019 and 2026, obtained through Google Scholar, Garuda, and several national and international journals. The articles were selected based on inclusion and exclusion criteria and then analyzed using qualitative descriptive methods.   Research Results : The results of the study show that most articles conclude that the rupiah exchange rate has an impact on Indonesia’s exports. A depreciation in the rupiah exchange rate tends to increase the competitiveness of Indonesian products, thereby boosting exports. However, some studies show that exchange rates do not have a significant impact on exports because other factors, such as Gross Domestic Product (GDP), are more dominant. Differences in research findings are influenced by differences in the research subjects, the research period, the methods of analysis, and the variables used. The rupiah exchange rate is one of the factors affecting Indonesia’s exports, although its influence is not absolute. This study is expected to serve as a reference for future research in further exploring the factors that influence Indonesia’s exports.